Beispiel Nr: 41
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y= 2x^2-\frac{2}{3}x-2\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y= 2x^2-\frac{2}{3}x-2\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=2x^2-\frac{2}{3}x-2 \\ y=2(x^2-\frac{1}{3}x-1) \\ y=2(x^2-\frac{1}{3}x+\left(\frac{1}{6}\right)^2-\left(\frac{1}{6}\right)^2-1) \\ y=2[(x-\frac{1}{6})^2-\left(\frac{1}{6}\right)^2-1] \\ y=2[(x-\frac{1}{6})^2-\frac{1}{36}-1] \\ y=2[(x-\frac{1}{6})^2-1\frac{1}{36}] \\ y=2(x-\frac{1}{6})^2-2\frac{1}{18} \\ Scheitel(\frac{1}{6}/-2\frac{1}{18}) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=2x^2-\frac{2}{3}x-2 \\ y=2(x^2-\frac{1}{3}x)-2 \\ y=2(x^2-\frac{1}{3}x+\left(\frac{1}{6}\right)^2-\left(\frac{1}{6}\right)^2)-2 \\ y=2[(x-\frac{1}{6})^2-\left(\frac{1}{6}\right)^2]-2 \\ y=2[(x-\frac{1}{6})^2-\frac{1}{36}]-2 \\ y=2(x-\frac{1}{6})^2-\frac{1}{18}-2 \\ y=2(x-\frac{1}{6})^2-2\frac{1}{18} \\ Scheitel(\frac{1}{6}/-2\frac{1}{18}) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=2x^2-\frac{2}{3}x-2 \\ xs=-\frac{-\frac{2}{3}}{2\cdot 2} \\ xs=\frac{1}{6} \\ ys=-2-\frac{\left(-\frac{2}{3}\right)^2}{4\cdot2} \\ ys=-2\frac{1}{18} \\ Scheitel(\frac{1}{6}/-2\frac{1}{18})\\ y=2(x-\frac{1}{6})^2-2\frac{1}{18} \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = [(-2\frac{1}{18});\infty[ \\ \\=2(x+0,847)(x-1,18)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y= 2x^2-\frac{2}{3}x-2 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ 2x^{2}-\frac{2}{3}x-2 =0 \\ x_{1/2}=\displaystyle\frac{+\frac{2}{3} \pm\sqrt{\left(-\frac{2}{3}\right)^{2}-4\cdot 2 \cdot \left(-2\right)}}{2\cdot2} \\ x_{1/2}=\displaystyle \frac{+\frac{2}{3} \pm\sqrt{16\frac{4}{9}}}{4} \\ x_{1/2}=\displaystyle \frac{\frac{2}{3} \pm4,06}{4} \\ x_{1}=\displaystyle \frac{\frac{2}{3} +4,06}{4} \qquad x_{2}=\displaystyle \frac{\frac{2}{3} -4,06}{4} \\ x_{1}=1,18 \qquad x_{2}=-0,847 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ 2x^{2}-\frac{2}{3}x-2 =0 \qquad /:2 \\ x^{2}-\frac{1}{3}x-1 =0 \\ x_{1/2}=\displaystyle -\frac{-\frac{1}{3}}{2}\pm\sqrt{\left(\frac{\left(-\frac{1}{3}\right)}{2}\right)^2- \left(-1\right)} \\ x_{1/2}=\displaystyle \frac{1}{6}\pm\sqrt{1\frac{1}{36}} \\ x_{1/2}=\displaystyle \frac{1}{6}\pm1,01 \\ x_{1}=1,18 \qquad x_{2}=-0,847 \end{array}\\ \end{array}\\ \underline{x_1=-0,847; \quad1\text{-fache Nullstelle}} \\\underline{x_2=1,18; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-0,847&< x <&1,18&< x\\ \hline f(x)&+&0&-&0&+\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-\infty;-0,847[\quad \cup \quad]1,18;\infty[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-0,847;1,18[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$